Organic solar cell using polystyrene as donor additive and preparation method thereof
By introducing polystyrene into the donor layer of organic solar cells to form a nanoporous donor layer thin film, the problem of complexity and poor repeatability of process parameters of bulk heterojunction structure is solved, and the photoelectric conversion efficiency and stability of the device are significantly improved.
Patent Information
- Application Number
- CN202411729929.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
AI Technical Summary
The existing organic solar cell devices are based on bulk heterojunction structures, with complex process parameters and difficult to control, resulting in poor experimental repetition, limiting the commercial application of devices.
Polystyrene (PS) is used as the additive to the donor layer, and PS is introduced into the donor layer by sequential spin-coating deposition method to form a uniform and vertically distributed nanoporous donor layer film, thereby building a stable and efficient active layer structure.
The photoelectric conversion efficiency of organic solar cells has been improved, and the short-circuit current and filling factor have been significantly improved, achieving a more stable active layer structure and higher charge transfer efficiency.
Smart Images

Figure CN119653974A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to an organic solar cell using polystyrene as a donor additive and a preparation method thereof. Background Art
[0002] As people's living standards continue to improve, the demand for fossil energy is also increasing. This has caused increasingly serious energy and climate problems, such as energy depletion and greenhouse effect. Therefore, it is crucial to develop renewable energy. Organic solar cells have attracted widespread attention from scientific researchers due to their advantages such as low cost, light weight, mechanical flexibility and large-area roll-to-roll manufacturing. It can directly convert light energy into electrical energy, is a very promising clean energy technology, and can well meet the rapidly growing energy demand. In recent years, with the continuous development of non-fullerene acceptor materials, the photoelectric conversion efficiency of organic solar cell (OSCs) devices has exceeded 20%. Its highest efficiency device is based on the bulk heterojunction active layer (BHJ) structure. The BHJ structure has a small phase domain, which can effectively increase the contact area between the donor and the acceptor, which is conducive to the dissociation of excitons. However, due to the complex donor-acceptor interaction in the BHJ structure, the morphology optimization process is difficult to control, and a series of process parameters such as the donor-acceptor ratio, solvent type, annealing method and time will affect the phase separation structure of the active layer. This makes the experimental repeatability poor and also limits the commercial application of BHJ-OSCs devices.
[0003] To solve this problem, a two-step method called layer-by-layer solution processing (LbL) for active layer fabrication was developed. This method prepares the donor and acceptor separately by spin coating and has attracted widespread attention. The solvent of the acceptor layer will cause the lower donor polymer layer to swell, allowing the acceptor to penetrate and diffuse into the polymer layer to form a nanoscale bulk heterojunction region. Compared with the widely used BHJ structure, the solution-processed LbL structure enables the active layer to have an adjustable vertical phase distribution and an adjustable donor-acceptor interface, which is beneficial for charge transport. At the same time, the LbL construction method can regulate the donor and acceptor separately, and provides a solution to the morphological problems caused by the complex interaction between the donor and the acceptor. This structure is suitable for large-area preparation, regardless of the donor-acceptor ratio and their compatibility in organic solvents, and has good development potential. In addition, the LbL structure can also add additives to the donor layer or the acceptor layer separately, which is beneficial to further improve the performance of the device.
[0004] In general, most of the current organic solar cell devices are manufactured based on bulk heterojunction structures. The performance of such devices depends largely on the fine phase separation structure in the active layer. The formation of this phase separation structure is related to a series of process parameters, and the morphology after mixing will change with the influence of the external environment. It is difficult to stably control and has poor repeatability, which is not conducive to the expansion of photovoltaic devices from small-area devices in the laboratory to large-area devices in industry. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides an organic solar cell using polystyrene as a donor additive and a preparation method thereof, by doping polystyrene in the donor layer, which is an easy and effective method to assist the donor to form an ordered and fine film, thereby constructing a stable and efficient active layer structure, thereby improving the photoelectric conversion efficiency of OSCs.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides an organic solar cell, the structure of which includes, from bottom to top, an anode layer, a hole transport layer, an active layer, an electron transport layer and a cathode layer; the active layer is composed of a donor layer and an acceptor layer, the donor layer is PM6 doped with polystyrene (PS), and the acceptor layer is Y6.
[0008] Preferably, the doping amount of the polystyrene is 0.5-2 wt% of the mass of PM6. Further, the doping amount of the polystyrene is 0.25-1 wt% of the mass of PM6.
[0009] The present invention introduces PS into the donor layer additionally and utilizes the good compatibility between PS and PM6 to form a donor layer film with uniform and vertically distributed nanoporous material, which is beneficial to improving the penetration depth of the subsequent acceptor solution and the generation of a continuous acceptor phase, thereby forming an active layer structure with an ideal vertical distribution.
[0010] Preferably, the thickness of the hole transport layer is 30-40 nm, the thickness of the active layer is 100-120 nm, the thickness of the electron transport layer is 20-40 nm, and the thickness of the cathode layer is 100-130 nm.
[0011] Preferably, the anode layer is indium tin oxide, the hole transport layer is PEDOT:PSS, the electron transport layer is PDINN, and the cathode layer is silver.
[0012] The second aspect of the present invention provides a method for preparing the organic solar cell according to the first aspect, comprising the following steps:
[0013] S1. After the hole transport layer is spin-coated on the anode substrate layer, a PM6 solution containing polystyrene is spin-coated onto the surface of the hole transport layer to form a donor layer;
[0014] S2, spin coating the Y6 solution onto the surface of the donor layer to form an acceptor layer, and annealing to obtain an active layer;
[0015] S3, sequentially spin-coating an electron transport layer and evaporating a cathode layer on the active layer to obtain an organic solar cell.
[0016] Preferably, the preparation method of the PM6 solution containing polystyrene is: PM6 is prepared into a 7-9 mg / mL chloroform solution, PS is prepared into a 14-16 mg / mL chloroform solution, and then the two solutions are mixed, and stirred at 45-55°C for 10-20 minutes to obtain a PM6 solution containing PS.
[0017] Preferably, the spin coating in S1 has a rotation speed of 1500 to 2500 rpm and a time of 30 to 50 s.
[0018] Preferably, the annealing temperature in S2 is 80° C. to 100° C., and the annealing time is 8 to 10 minutes.
[0019] Preferably, the preparation method of the Y6 solution in S2 is: prepare Y6 into a 6-8 mg / mL chloroform solution, and then add 1-chloronaphthalene at a volume ratio of 99.5:0.5.
[0020] Preferably, the spin coating in S2 has a rotation speed of 2000 to 2600 rpm and a time of 30 to 50 s.
[0021] Preferably, when the anode substrate layer is ITO glass, a layer of PEDOT:PSS is spin-coated on the ITO glass and then annealed to form a hole transport layer. Further, the annealing temperature is 150°C for 15 minutes; the spin coating speed is 4000 rpm for 30 seconds.
[0022] When the electron transport layer is PDINN, the PDINN solution is spin-coated onto the active layer to form the electron transport layer. Further, the PDINN solution is a 1 mg / mL methanol solution; the spin-coating speed is 2500-3500 rpm, and the time is 20-40 seconds.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention discloses an organic solar cell using polystyrene as a donor additive and a preparation method thereof. The structure of the organic solar cell includes an anode layer, a hole transport layer, an active layer, an electron transport layer and a cathode layer from bottom to top; the active layer is composed of a donor layer and an acceptor layer; the donor layer is PM6 doped with polystyrene, and the acceptor layer is Y6. The present invention is based on a sequential spin coating deposition method. By additionally introducing PS into the donor layer, the appropriate compatibility difference between PS and PM6 is utilized to form a donor layer film with uniform and vertical distribution of nanoporous materials, which is beneficial to improve the penetration depth of the subsequent acceptor solution and the generation of a continuous acceptor phase, thereby forming an active layer structure with an ideal vertical distribution. Compared with the planar heterojunction active layer prepared by the conventional sequential spin coating deposition method, this active layer structure has more donor-acceptor interfaces, and can also maintain a continuous donor-acceptor phase, which is more conducive to the separation and transportation of excitons. This makes OCSs with an appropriate amount of PS introduced have higher photoelectric conversion efficiency than OSCs without PS, wherein both the short-circuit current and the fill factor are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A structure of an organic solar cell having polystyrene added to a donor layer;
[0026] Figure 2 The current density and voltage (JV) characteristic curve of the organic solar cell with polystyrene added to the donor layer;
[0027] Figure 3 Photovoltaic conversion efficiency (PCE) of organic solar cells with polystyrene added to the donor layer. DETAILED DESCRIPTION
[0028] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0029] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0030] Embodiment 1:
[0031] This embodiment provides an organic solar cell structure in which 0.5% (relative to the donor mass) of polystyrene (PS) is added to the donor layer.
[0032] The device structure ( Figure 1) comprises, from bottom to top, an anode layer, a hole transport layer, an active layer, an electron transport layer and a cathode layer, wherein the active layer is composed of a donor layer and an acceptor layer; the specific preparation method of the device structure comprises the following steps:
[0033] (1) Cleaning of the anode substrate layer: An ITO (indium tin oxide) glass transparent substrate is used as the anode substrate. The substrate (ITO) is first ultrasonically cleaned in an ultrasonic cleaner with deionized water, acetone, anhydrous ethanol, and isopropanol for 15 minutes. Then, the residual isopropanol on the glass surface is blown dry with a nitrogen gun to obtain a substrate with a clean surface.
[0034] (2) Preparation of hole transport layer: The washed and dried ITO was plasma treated for 10 minutes. Then, a PEDOT:PSS solution (model: 4083) was spin-coated on the ITO surface at a speed of 4500 rpm for 30 seconds. Finally, the PEDOT:PSS was annealed at 150°C for 10 minutes to obtain a PEDOT:PSS-based hole transport layer with a thickness of 30 to 40 nm.
[0035] (3) Preparation of active layer with PS added: PM6 (cas number: 1802013-83-7), PS and Y6 (cas number: 2304444-49-1) were prepared into chloroform solutions of 8 mg / mL, 15 mg / mL and 7 mg / mL, respectively, and heated and stirred at 50°C for 5 hours to ensure full dissolution. Then, 1-chloronaphthalene was added to the Y6 solution at a volume ratio of 99.5:0.5 to prepare the acceptor solution, and 0.5 wt% (relative to the donor mass) of PS solution was added to the PM6 solution to prepare the donor solution, and heated to 50°C and stirred for 15 minutes. The donor solution was then spin-coated on the PEDOT:PSS hole transport layer at 2000 rpm for 40 seconds to form a film, and then the acceptor solution was spin-coated on the donor layer at 2300 rpm for 40 seconds to form a film. Finally, the substrate was placed at 80°C for thermal annealing for 8 minutes to obtain the active layer. The overall thickness of the active layer was 100-120 nm.
[0036] (4) Preparation of electron transport layer: PDINN was prepared into a 1 mg / mL methanol solution and then spin-coated on the active layer at 3000 rpm for 30 seconds to obtain an electron transport layer with a thickness of 20 to 40 nm.
[0037] (5) Preparation of cathode layer: Metal Ag was evaporated onto the electron transport layer using a vacuum evaporator to form a cathode layer. The evaporation process was performed at 8×10 -5 Pa vacuum, the thickness of the cathode layer is 100-130nm, that is, an organic solar cell with polystyrene added to the donor layer is prepared, and its structure is as follows Figure 1 shown.
[0038] Embodiment 2:
[0039] This embodiment also provides an organic solar cell structure with polystyrene (PS) added to the donor layer. The structure and preparation method of the device are substantially the same as those of Example 1, except that 0.25 wt% (relative to the donor mass) of PS solution is added to the PM6 solution.
[0040] Embodiment 3:
[0041] This embodiment also provides an organic solar cell structure in which polystyrene (PS) is added to the donor layer. The structure and preparation method of the device are substantially the same as those of Example 1, except that 1 wt% (relative to the donor mass) of PS solution is added to the PM6 solution.
[0042] Embodiment 4:
[0043] This embodiment also provides an organic solar cell structure in which polystyrene (PS) is added to the donor layer. The structure and preparation method of the device are substantially the same as those of Example 1, except that 2 wt% (relative to the donor mass) of PS solution is added to the PM6 solution.
[0044] Comparative Example 1:
[0045] This embodiment also provides an organic solar cell structure in which polystyrene (PS) is added to the donor layer. The structure and preparation method of the device are substantially the same as those of Embodiment 1, except that no PS solution is added to the PM6 solution.
[0046] Experimental example:
[0047] The performance parameters of the organic solar cells of Examples 1 to 4 and Comparative Example 1 were tested. The results are shown in Tables 1 and Figure 1 , 2 shown.
[0048] As can be seen from Table 1, after adding a certain amount of PS to the donor material, the short-circuit current and fill factor of the device are effectively improved. When the PS addition mass is 0.5% of the donor material mass, the best photoelectric conversion efficiency is reached, which is as high as 17.12%, significantly exceeding the device without adding PS (comparative example). It is also one of the highest efficiencies in OSCs based on PM6:Y6 active layer system prepared by sequential spin coating. This shows that the introduction of PS improves the charge transfer and separation of the device and reduces the recombination probability of excitons.
[0049] from Figure 2 , 3 It can also be seen that after adding an appropriate amount of PS, the photoelectric conversion efficiency of the device is significantly improved.
[0050] Table 1 Performance parameters of organic solar cells of Examples 1 to 4 and Comparative Example 1
[0051]
[0052] In summary, the present invention adopts a layered preparation method based on the sequential spin coating deposition method to improve the efficiency of OCSs devices by introducing PS additives into the donor layer PM6. Compared with the planar heterojunction active layer prepared by the conventional sequential spin coating deposition method, this active layer structure has more donor-acceptor interfaces, while also maintaining a continuous donor-acceptor phase, which is more conducive to the separation and transportation of excitons. This makes OCSs that introduce an appropriate amount of PS have a higher photoelectric conversion efficiency than OSCs that do not introduce PS, with a significant improvement in short-circuit current and fill factor.
[0053] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. An organic solar cell, characterized in that: The structure of the organic solar cell includes, from bottom to top, an anode layer, a hole transport layer, an active layer, an electron transport layer and a cathode layer; the active layer is composed of a donor layer and an acceptor layer, the donor layer is PM6 doped with polystyrene (PS), and the acceptor layer is Y6.
2. An organic solar cell according to claim 1, characterized in that: The doping amount of the polystyrene is 0.5-2wt% of the mass of PM6.
3. The organic solar cell according to claim 1, characterized in that: The thickness of the hole transport layer is 30-40 nm, the thickness of the active layer is 100-120 nm, the thickness of the electron transport layer is 20-40 nm, and the thickness of the cathode layer is 100-130 nm.
4. The organic solar cell according to claim 1, characterized in that: The anode layer is indium tin oxide, the hole transport layer is PEDOT:PSS, the electron transport layer is PDINN, and the cathode layer is silver.
5. The method for preparing an organic solar cell according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. After the hole transport layer is spin-coated on the anode substrate layer, a PM6 solution containing polystyrene is spin-coated onto the surface of the hole transport layer to form a donor layer; S2, spin coating the Y6 solution onto the surface of the donor layer to form an acceptor layer, and annealing to obtain an active layer; S3, sequentially spin-coating an electron transport layer and evaporating a cathode layer on the active layer to obtain an organic solar cell.
6. The method for preparing an organic solar cell according to claim 5, characterized in that: The preparation method of the PM6 solution containing polystyrene is: PM6 is prepared into a chloroform solution of 7-9 mg / mL, PS is prepared into a chloroform solution of 14-16 mg / mL, and then the two solutions are mixed, and stirred at 45-55° C. for 10-20 minutes to obtain a PM6 solution containing PS.
7. The method for preparing an organic solar cell according to claim 5, characterized in that: The spin coating speed in S1 is 1500-2500 rpm, and the time is 30-50 s.
8. The method for preparing an organic solar cell according to claim 5, characterized in that: The annealing temperature in S2 is 80° C. to 100° C., and the annealing time is 8 to 10 minutes.
9. The method for preparing an organic solar cell according to claim 5, characterized in that: The preparation method of the Y6 solution described in S2 is: prepare Y6 into a 6-8 mg / mL chloroform solution, and then add 1-chloronaphthalene at a volume ratio of 99.5:0.
5.
10. The method for preparing an organic solar cell according to claim 5, characterized in that: The spin coating speed in S2 is 2000-2600 rpm, and the time is 30-50 s.
Citation Information
Patent Citations
Organic solar cell using polylactic acid as donor additive and preparation method thereof
CN117279400A